PENANAMAN NILAI KEDISIPLINAN MELALUI KEGIATAN EKSTRAKURIKULER PRAMUKA SMPN 2 PONTIANAK - Sakinah, Sakinah; Parijo, Parijo; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe title of the study was "Raising the Value of Discipline through Scouting Extracurricular Activities in Junior High School 2 Pontianak". The general problem was how is the process of raising discipline values through Scout extracurricular activities? The sub-problem was how is the process of raising disciplinary values through Scout extracurricular activities, and how are the results of the raising of values of discipline through Scout extracurricular activities? The purpose of the study was to determine the process of raising the value of discipline through Scout extracurricular activities. The approach used was a qualitative approach with descriptive methods. Data collection techniques used are observation, interview and documentation study techniques. The analysis in this study was presented descriptively qualitatively by using informants as many as 5 people, namely 1 supervisor and 4 Scouts. The results of the study show that the process of cultivating disciplinary values applied by Scout extracurricular activities was done through moral knowing, moral feeling and moral action. The moral process was knowing the value of discipline carried out in Scout extracurricular activities by providing understanding through advice. The moral feeling process was done by giving a good example. While the moral action process is carried out by practicing values obtained from the results of the moral knowing and moral feeling.Keywords: Discipline, Raising Value, Scouts